Relationship between inflammation, the gut microbiota, and metabolic osteoarthritis development: studies in a rat model. Issue 11 (November 2015) - Collins, K.H.; Paul, H.A.; Reimer, R.A.; Seerattan, R.A.; Hart, D.A.; Herzog, W.
Summary: Osteoarthritis (OA) may result from intrinsic inflammation related to metabolic disturbance. Obesity-associated inflammation is triggered by lipopolysaccharide (LPS) derived from the gut microbiota. However, the relationship between gut microbiota, LPS, inflammation, and OA remain unclear. Objective: To evaluate the associations between gut microbiota, systemic LPS levels, serum and local inflammatory profiles, and joint damage in a high fat/high sucrose diet induced obese rat model. Methods: 32 rats were randomized to a high fat/high sucrose diet (diet-induced obese (DIO), 40% fat, 45% sucrose, n  = 21) or chow diet group (12% fat, 3.7% sucrose n  = 11) for 28 weeks. After a 12-week obesity induction period, DIO animals were stratified into Obesity Prone (DIO-P, top 33% by change in body mass, n  = 7), and Obesity Resistant groups (DIO-R, bottom 33%, n  = 7). At sacrifice, joints were scored using a Modified Mankin Criteria. Blood and synovial fluid analytes, serum LPS, and fecal gut microbiota were analyzed. Results: DIO animals had greater Modified Mankin scores than chow animals ( P  = 0.002). There was a significant relationship ( r  = 0.604, p  = 0.001) between body fat, but not body mass, and Modified Mankin score. Eighteen synovial fluid and four serum analytes were increased in DIO animals. DIO serum LPS levels were increased compared to chow ( P  = 0.031). Together, Lactobacillus species (spp.) and Methanobrevibacter spp. abundance had a strong predictive relationship with Modified Mankin Score ( r 2  = 0.5, P  < 0.001). Conclusions: Increased OA in DIO animals is associated with greater body fat, not body mass. The link between gut microbiota and adiposity-derived inflammation and metabolic OA warrants further investigation.